2012
DOI: 10.2147/ijn.s33261
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light irradiation upon photodynamic therapy based on 5-aminolevulinic acid–gold nanoparticle conjugates in K562 cells via singlet oxygen generation

Abstract: Purpose: As a precursor of the potent photosensitizer protoporphyrin IX (PpIX), 5-aminolevulinic acid (5-ALA), was conjugated onto cationic gold nanoparticles (GNPs) to improve the efficacy of photodynamic therapy (PDT). Methods: Cationic GNPs reduced by branched polyethyleneimine and 5-ALA were conjugated onto the cationic GNPs by creating an electrostatic interaction at physiological pH. The efficacy of ALA-GNP conjugates in PDT was investigated under irradiation with a mercury lamp (central wavelength of 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 46 publications
2
36
0
Order By: Relevance
“…The major reasoning is that increased lipophilicity potentially improves the passage through biological membranes thus increasing intracellular substrate concentration for heme biosynthesis. Recently, substantial efforts have also been directed towards nanocarriers loaded [20][21][22][23][24] or conjugated [25][26][27][28] with 5-ALA. These approaches tackle some of the pharmacokinetic and specificity drawbacks of 5-ALA but have so far failed to produce a clinical candidate for the improved delivery of 5-ALA mostly due to high 5-ALA loading and delivery required for this type of FPD or PDT.…”
Section: Introductionmentioning
confidence: 99%
“…The major reasoning is that increased lipophilicity potentially improves the passage through biological membranes thus increasing intracellular substrate concentration for heme biosynthesis. Recently, substantial efforts have also been directed towards nanocarriers loaded [20][21][22][23][24] or conjugated [25][26][27][28] with 5-ALA. These approaches tackle some of the pharmacokinetic and specificity drawbacks of 5-ALA but have so far failed to produce a clinical candidate for the improved delivery of 5-ALA mostly due to high 5-ALA loading and delivery required for this type of FPD or PDT.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings in PDT on the Mel-Rm cell line showed, ED50 was reduced from 136.2 J/cm 2 for 5ALA to 56.2 J/cm 2 in the presence of the conjugate. Xu et al produced another study that has also shown the increasing efficiency of PDT (Xu et al 2012). This indicates that the presence of the conjugate leads to a more than two-fold increase in the efficiency of PDT on Mel-Rm cells in comparison to 5ALA alone.…”
Section: Discussionmentioning
confidence: 99%
“…Protoporphyrin IX (PpIX) is produced in cells via the heme synthesis pathway, from the substrate aminolevulinic acid (5ALA), and is known as a high bio-compatible photosensitizer (Kim et al 2011, Sultan et al 2006. Previous studies have shown that gold nanoparticles can act as the carrier for 5ALA and in the presence of the 5ALA-conjugated gold nanoparticles will result in increased efficiency of PDT (Hainfeld et al 2004, Xu et al 2012. Therefore, the conjugate can be considered as an effective photosensitizer that approximately covers the first problem of PDT.…”
Section: Introductionmentioning
confidence: 99%
“…About the results achieved, one assumption is entrance of cisplatin in the presence of GNPs that facilitated. It has shown GNPs with a diameter less than 100 nm enhance endocytosis and permeability and retention effect (EPR) (37)(38)(39). This mechanism has often resulted in 10-fold or greater drug delivery to a tumor over conventional chemotherapy (40).…”
Section: Discussionmentioning
confidence: 99%